Human podocytes responses to alternatively spliced Extra domain A Fibronectin in culture - Madne, Tarunkumar Hemraj; Dockrell, Mark Edward Carl (Cellular and Molecular Biology, 2018)
The interactions of the extracellular matrix (ECM) proteins with cells strongly regulate cell behaviour. The glomerular basement membrane (GBM) is a dynamic structure made up of protein secreted by endothelial cells and podocyte. These proteins could regulate the behaviour of these cells in health and diseases. Extra Domain A + Fn (EDA+Fn) is an alternatively spliced form of Fibronectin (Fn) recently identified in GBM and a recognised marker of various pathologies. In this study for the first time, we have investigated the responses of human podocytes cultured on different composition of GBM proteins which are cellular Fn (EDA+), plasma Fn (EDA-) and collagen IV. Conditionally immortalised human podocyte were grown on the dishes coated with different matrices; collagen IV (Col IV), cellular fibronectin (CFn) containing the EDA Exon, plasma fibronectin (PFn), which lacks the EDA Exon (EDA-Fn). We have performed western blotting to characterise the expression of the different proteins, real time PCR and RT-PCR to look for gene expression and alternative splicing of EDA+Fn. We have used TGFÎ²1 as a stimulator. We have used HEK-Blue-hTLR4 cells to determine the biological activity of cellular Fn. Conditionally immortalised human podocyte show marked differences in their morphology grown on the dishes coated with different matrices; Col IV, CFn, and PFn. CFn was biologically active as it activated the TLR4 signalling in HEK-Blue-hTLR4 cells. Different matrices effects basal as well as TGFÎ²1 mediated alternative splicing of EDA+Fn. TGFÎ²1 was active on different matrices as it induced phosphorylation of pSmad3 however it did not affect phosphorylation of pAkt and p38. Interestingly, different cellular matrices affected basal phosphorylation of pAkt. CFn downregulated gene expression of synaptopodin and increased gene expression of collagen I and Fn. CFn increased cell death in detached human podocytes. Alteration of the constituents of the GBM is likely to significantly alter podocyte cellular responses to growth factors involved in podocytopathies, such as TGFÎ².